Analysis of Supply Chain Risks to the Distribution of Cancer Medicine with AHP (Analytical Hierarchy Process) Methods - Nasihardani, Dana; Sudarto, Sumarsono; Ichiarto, Bonivasius Prasetya (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2026)
This study explores the evolving landscape of supply chain management (SCM) as a critical factor that transcends competition between individual firms and emphasizes collaboration in supply chains. In healthcare, health insurance provides a safety net against  the uncertainties of life, especially cancer, the world's second leading killer. The study focuses on addressing drug delivery delays in cancer care supply chains using the Analytical Hierarchy Process (AHP) and SWOT analysis. Based on SCM concepts, medical supply chain risk management, and AHP methodology, the study uses a qualitative approach that includes data collection on anticancer drug abuse and  focus group discussion (FGD). The AHP hierarchy, which emphasizes timeliness of delivery, highlights two prominent options: direct distribution to hospitals and a hybrid distribution model. A comprehensive SWOT analysis prioritizes key factors, with an emphasis on timeliness, and identifies direct marketing as the most important opportunity for hospitals, highlighting its strategic importance in optimizing the distribution of cancer drugs. The study highlights the need for timely and efficient healthcare supply chains to combat the global cancer problem.